Balancing the basal ganglia circuitry: A possible new role for dopamine D2 receptors in health and disease. Issue 7 (28th May 2015) - Cazorla, Maxime; Kang, Un Jung; Kellendonk, Christoph
Abstract Current therapies for treating movement disorders such as Parkinson's disease are effective but limited by undesirable and intractable side effects. Developing more effective therapies will require better understanding of what causes basal ganglia dysregulation and why medication‐induced side effects develop. Although basal ganglia have been extensively studied in the last decades, its circuit anatomy is very complex, and significant controversy exists as to how the interplay of different basal ganglia nuclei process motor information and output. We have recently identified the importance of an underappreciated collateral projection that bridges the striatal output direct pathway with the indirect pathway. These bridging collaterals are extremely plastic in the adult brain and are involved in the regulation of motor balance. Our findings add a new angle to the classical model of basal ganglia circuitry that could be exploited for the development of new therapies against movement disorders. In this Scientific Perspective, we describe the function of bridging collaterals and other recent discoveries that challenge the simplicity of the classical basal ganglia circuit model. We then discuss the potential implication of bridging collaterals in the pathophysiology of Parkinson's disease and schizophrenia. Because dopamine D2 receptors and striatal neuron excitability have been found to regulate the density of bridging collaterals, we propose that targeting these projections downstream of D2 receptors could be a possible strategy for the treatment of basal ganglia disorders. © 2015 International Parkinson and Movement Disorder Society